THE INFLUENCE OF WORK ENVIRONMENT, WORK MOTIVATION AND WORK ETHIC ON EMPLOYEE PRODUCTIVITY AT THE MAPPI REGENCY REGIONAL SECRETARIAT OFFICE - Klaveryus Irvan Pakka; Arius Andreas Kambu; Ikhwan HS (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The Mappi Regional Secretariat, responsible for critical administrative and coordination functions in local government, has faced challenges in employee productivity as evidenced by suboptimal Community Satisfaction Index scores over a three-year period, averaging only 72% of the target. Despite efforts to improve productivity through strategic planning and infrastructure upgrades, human resource issues persist. The report explores how the Work Environment, Work Motivation, and Work Ethic affect Employee Productivity at the Mappi Regency Regional Secretariat Office. A quantitative research approach was utilised for this study. The target population was all mayoral officers at the regional secretariat in Mappi, totaling 153 individuals. A sample size of 114 was selected for the research. A questionnaire was employed as the research instrument. The study encompassed 4 variables: Work environment (X1), Work motivation (X2), Work Ethic (X3), and Performance (Y). Data analysis involved Descriptive Analysis of Respondent Schedule and Descriptive Statistical Analysis. Quality tests were conducted to ensure data validity and reliability, including Normality Test, Heteroscedasticity Test, Multicollinearity Test, and Autocorrelation Test. The study also included multiple linear regression tests, correlation tests, determination coefficient, and hypothesis testing (t-Test and f-Test). The findings indicated that the work environment, work motivation, and work ethic positively and significantly impacted the productivity of Mappi Regional Secretariat employees. Work ethic displayed a particularly strong positive influence on work productivity compared to other variables. It is recommended that employees at Mappi Regional Secretariat uphold their work ethic, as it plays a crucial role in enhancing work productivity.